Students’ Difficulties in Constructing Paragraph Writing by Using Regular and Irregular - Tri Setianingsih; Baiq Zuhrotun Nafisah (LPPM Universitas Bumigora Mataram, 2023)
This study was raised from the problems of students’ difficulties in constructing paragraph by using regular and irregular at the second-grade student of Madrasah Aliyah Swasta Jannah Nadhatul Wathan Ampenan. The aimed of this study were; the first, to find out the students’ difficulties in constructing paragraph writing. The second, to find out the causes of students’ difficulties in using regular and irregular forms. This study used qualitative research. The data were collected by using written test and questionnaires. The first result showed that the most common students’ difficulties was in using Verb 2 simple past on irregular verb forms with 20 difficulties or 100% and the second common students’ difficulties was in using Verb 1 (base form) with 12 difficulties or 60%, and the third common students’ difficulties was in using Verb +ed (simple past) on regular verb forms with 12 difficulties or 60%, the fourth common students’ difficulties was in using Verb 3 (past participle) on irregular verb with 8 difficulties or 40%, and the last students’ difficulties was in using V+ing participle with 4 difficulties or 20%.The second result showed that the causes of students’ difficulties found on three aspects; psychological, environment and non-social environment aspects. In psychological, there were 95% students had problem with his/her intelligence in mastering English material. In environment aspect, there were 75% students did not get an attention from his/her parents. In non-social environment aspect, there were 70% students had problem with the material that was given by the teacher, 60% students lacked of the teacher’s attention.